2021
DOI: 10.1016/j.jaim.2021.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of Annona reticulata L. leaf extract on antihyperglycemic activity and its hepato-renal protective potential in streptozotocin induced diabetic rats

Abstract: Background Annona reticulata L. is a traditionally important plant due to its versatile source of medicine and industrial products. It is used to treat cardiac problems, wound healing, diabetes, ulcers and bacterial infections. As it is a commercial fruit bearing plant, wide range studies on this plant reaches the mankind efficiently. Objective(s) The present study was focussed on antihyperglycemic potential of A. reticulata lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…In the current investigation, hepatocyte injury was indicated by a substantial rise in liver function parameters (p<0.05) in the serum of the STZ-induced diabetic control rat group which collaborated with the report of Pulivarthi et al 39 . According to Al-Bahrani 40 and Saleh et al 38 , high levels of these enzymes in the serum of STZ-induced diabetic rats represent hepatocyte damage.…”
Section: Discussionsupporting
confidence: 89%
“…In the current investigation, hepatocyte injury was indicated by a substantial rise in liver function parameters (p<0.05) in the serum of the STZ-induced diabetic control rat group which collaborated with the report of Pulivarthi et al 39 . According to Al-Bahrani 40 and Saleh et al 38 , high levels of these enzymes in the serum of STZ-induced diabetic rats represent hepatocyte damage.…”
Section: Discussionsupporting
confidence: 89%
“…It is reported that 463 million people are suffering from diabetes mellitus around the world until 2019 (IDF, 2019) while the main patient is type 2 diabetes mellitus (T2DM), which accounts for 90% of all diabetic cases (Lee & Li, 2021). T2DM is principally caused by insulin resistance (IR) and insulin secretion disorders and IR is believed as the initiating factor in the development of T2DM (American Diabetes Association, 2016; Pulivarthi & Naidu, 2021). When IR occurs in the body, islet beta cells will facilitate insulin production to compensate for IR which to maintain blood glucose level (Diabetes Care, 2015).…”
Section: Introductionmentioning
confidence: 99%